(untitled) - Holmes, Phil; Phil Holmes (London, 1998)
This book presents a range of investment appraisal methods and models to help readers make good investment decisions. Each approach is thoroughly described, evaluated, and illustrated using examples, with its assumptions and limitations analyzed in terms of their implications for investment decision-making practice. Getting investment decisions right is crucial but due to a complex and dynamic business environment this remains a challenging management task
Keywords: Capital investments; Capital investments